Oxidation of carbohydrate feedings during prolonged exercise: current thoughts, guidelines and directions for future research - Jeukendrup, A. E.; Jentjens, R. (Sports Medicine, 2000)
Although it is known that carbohydrate (CHO) feedings during exercise improve endurance performance, the effects of different feeding strategies are less clear. Studies using (stable) isotope methodology have shown that not all carbohydrates are oxidised at similar rates and hence they may not be equally effective. Glucose, sucrose, maltose, maltodextrins and amylopectin are oxidised at high rates. Fructose, galactose and amylose have been shown to be oxidised at 25 to 50% lower rates. Combinations of multiple transportable CHO may increase the total CHO absorption and total exogenous CHO oxidation. Increasing the CHO intake up to 1.0 to 1.5 g/min will increase the oxidation up to about 1.0 to 1.1 g/min. However, a further increase of the intake will not further increase the oxidation rates. Training status does not affect exogenous CHO oxidation. The effects of fasting and muscle glycogen depletion are less clear. The most remarkable conclusion is probably that exogenous CHO oxidation rates do not exceed 1.0 to 1.1 g/min. There is convincing evidence that this limitation is not at the muscular level but most likely located in the intestine or the liver. Intestinal perfusion studies seem to suggest that the capacity to absorb glucose is only slightly in excess of the observed entrance of glucose into the blood and the rate of absorption may thus be a factor contributing to the limitation. However, the liver may play an additional important role, in that it provides glucose to the bloodstream at a rate of about 1 g/min by balancing the glucose from the gut and from glycogenolysis/gluconeogenesis. It is possible that when large amounts of glucose are ingested absorption is a limiting factor, and the liver will retain some glucose and thus act as a second limiting factor to exogenous CHO oxidation.